Le discours rapporté à l’épreuve de la représentation de la pensée dans Night and Day de Virginia Woolf : degré de vraisemblance - Alexandra PEDINIELLI-FÉRON (E-REA)
This article aims at studying in what ways the three major types of reported speech, namely direct speech, free indirect speech and indirect speech, give a more or less lifelike representation of the characters' thought in Virginia Woolf's Night and Day, a novel in which the characters' inner life is at stake. It presents the characteristics that define them and that distinguish them from reported speech representing external speech.